Upgrading Waste Management and Sustainability Reporting in Banking Industry – Evidence from Serbia - Knežević, Goranka; Pavlović, Vladan; Stevanovic, Simo (Industrija, 2018)
This paper examines banking industry practice in the area of circular economy reporting with the specific emphasis on waste management reporting in this sector. Paper answers the basic question – is financial service sector exempt from the circular economy reporting requirements having low material usage and resource consumption? Manuscript indicates that in Serbia waste management reporting in banks is in the early stage. Most of the waste management indicators in banks are included as integral part of sustainability reports or as part of management report. Paper indicates that less than half of the bank population in Serbia prepares standard report required by the Environmental Protection Agency. Having in mind these results, banks managers and state officials should take into consideration the fact that most of the banks do not report on flow of waste and most of these indicators are not regularly published on website implying that stakeholders and investors are not adequately informed on the inclusion of banks into circular economy environment. Lagging behind waste management requirements could be potentially hazardous having in mind the fact that Serbia strives towards European Union membership where the legislation and practical alignment with the EU regulation is inevitable process.